The Sinai Desert (Revista de Estudos Orientais, 2021)
A fantastic place. Inhospitable. Extremely dry. The setting for one of the most extraordinary narratives in the Hebrew Bible: the granting of the Decalogue to humanity. The Sinai Desert is a real, authentic place where the Israelites passed on their journeys towards the Promised Land, as did the prophet Elijah centuries later. This article seeks to study the Sinai desert through the analysis of the meaning of the name of the place, Biblical and Talmudic data, historical, geographical and archaeological details.